PENDAMPINGAN LITERASI BACA ALQURAN PADA ANAK TPA MASJID AL-FALAH, TABING MELALUI SUDUT BACA KREATIF - Cisia Padila; Martin Kustati; Gusmirawati Gusmirawati (LPPM Universitas Bina Bangsa, 2023)
The purpose of this community service is to familiarise children in reading and improve children's ability to understand the Qur'an. In this service, the children of TPA Nurul Falah are taught first to read verse by verse in the Qur'an then at the end there will be a test of how well the children understand what they have learned. The existence of literacy assistance in reading the Qur'an for TPA children is carried out to overcome this, researchers have provided literacy assistance in reading the Qur'an for early childhood at the al-falah mosque. In this literacy assistance, researchers make efforts, namely by providing a creative reading corner where researchers and other friends provide reading books and iqro' books that researchers get from donations from many parties through various media to then be used as learning materials for children around the al-falah Tabing mosque. In each meeting, mentors will guide children to learn to read the Qur'an and discuss homework given by teachers at school. This research uses the counselling method and continues with the consultation method between mentors and related children if further problems or difficulties are found. The output of this research is to make children familiar with the world of literacy and make children like this world of literacy. From the research conducted, it was found that children have